Determining rates of sediment accumulation on the Mekong shelf: Timescales, steady-state assumptions, and radiochemical tracers. (1st September 2017) - DeMaster, D.J.; Liu, J.P.; Eidam, E.; Nittrouer, C.A.; Nguyen, T.T.
Abstract: Thirty-two kasten cores, collected from the proximal Mekong continental shelf, have been analyzed for their excess 210 Pb distributions in an effort to establish rates of sediment accumulation over the past 100 years. The length of the cores varied from 0.5 to 3 m, and stations sampled topset, foreset, and bottomset beds (water depths 7–21 m). Apparent excess 210 Pb sediment accumulation rates ranged from > 10 cm/y (no down-core decrease of excess activity over 300 cm core length) near the Song Hau river mouth, to 1–3 cm/y in topset and foreset beds within 20–50 km of the river mouth, to rates as low as 0.4 cm/y in cores from bottomset beds. The 210 Pb sediment accumulation rates yield an overall sediment burial rate of 6.1 × 10 13  g/y for the proximal deltaic deposits, which corresponds to 43% of the total modern Mekong sediment burial on the southern Vietnam shelf (1.4 × 10 14  g/y; based on our 210 Pb and seismic data and 210 Pb data from the literature). This shelf burial rate is in reasonable agreement with current long-term estimates of Mekong River sediment discharge (1.3–1.6 × 10 14  g/y) from the literature. The inventory of excess 210 Pb in the proximal Mekong deltaic deposits indicates that the shoreward flow of offshore water (entrained during river/ocean mixing) is approximately twice the flow of the Mekong freshwater discharge. Organic-carbon 14 C ages were measured on 10 cores from the proximal Mekong delta and compared to 210 Pb sediment accumulation rates in the same core. The 210 Pb accumulation rates in all 10 cores were considered to be more robust and accurate than the 14 C geochronologies, primarily because of down-core variations in the source of organic carbon deposited on the seafloor (old terrestrial carbon versus younger marine carbon). Variations in the source of organic carbon accumulating in the seabed were resolved by measuring the δ 13 C value of the seabed organic carbon. Highlights: The first sediment budget for the subaqueous Mekong delta in the literature. The 100-year sedimentation rate in the Mekong subaqueous delta is 1.4×10 14 g/y. The 210 Pb mass accumulation rate equals the long-term sediment discharge rate. One third of the subaqueous delta accumulation occurs in the proximal deposits. In the complex Mekong deltaic environment 210 Pb geochronology is more robust than 14 C. Based on 210 Pb, onshore flow of offshore water is 2X the Mekong River discharge rate.